STRATEGI DINAS PARIWISATA KABUPATEN KLUNGKUNG DALAM PENGEMBANGAN PARIWISATA DI KECAMATAN NUSA PENIDA - Mustika, Kadek; Yasintha, Putu Nomy; Wirantari, I Dewa Ayu Putri (CITIZEN CHARTER, 2022)
Nusa Penida District has tourism potential with its natural beauty. Penida District is divided into three islands, namely Nusa Penida Island, Nusa Lembongan Island, and Nusa Ceningan Island. The purpose of this study is the extent to which the strategy set by the Klungkung Regency Tourism Office in tourism development in Nusa Penida District. The theory used is the theory of strategic planning according to John Bryson and the theory of SWOT analysis according to Sondang P. Siagian. This research uses descriptive qualitative method. The results showed that the strategy of the Klungkung Regency Tourism Office in Tourism Development in Nusa Penida District had been going well but not yet optimal because there were planning and implementation constraints in the field. This research produces recommendations for improving road access, expanding parking lots, building tourist attraction facilities, making events attract tourists.